On a Third-Order System of Difference Equations with Variable Coefficients - Stevo Stević; Josef Diblík; Bratislav Iricanin; Zdenek Šmarda (Abstract and Applied Analysis)
We show that the system of three difference equations xn+1=an(1)xn-2/(bn(1)ynzn-1xn-2+cn(1)), yn+1=an(2)yn-2/(bn(2)znxn-1yn-2+cn(2)), and zn+1=an(3)zn-2/(bn(3)xnyn-1zn-2+cn(3)), n∈N0, where all elements of the sequences an(i), bn(i), cn(i), n∈N0, i∈{1,2,3}, and initial values x-j, y-j, z-j, j∈{0,1,2}, are real numbers, can be solved. Explicit formulae for solutions of the system are derived, and some consequences on asymptotic behavior of solutions for the case when coefficients are periodic with period three are deduced.